Analisis Desain Institusional dalam Seleksi Pantia Pemilihan Kecamatan Kabupaten Sukoharjo Untuk Pemilu Tahun 2024 - Rico Dwi Setiawan; Ahmad Zaki Fadlur Rohman (HK-Publishing, 2023)
AbsratctThis study discusses how institutional design forms in KDP selection in Sukoharjo Regency. The formation of the PPK or Sub-District Election Committee is the KPU's full authority for each regency or city. In this study, the PPK selection process in Sukoharjo Regency will be examined, including how the selection process works and the various indicators that influence the selection results for prospective PPK members, especially in the regulations, namely PKPU No. 8 Year 2022 and KPU Decree No. 476 Year 2022. In analyzing the institutional design in the KDP selection process for Sukoharjo Regency, researchers used Elinor Ostrom's Institutional Analysis and Development theory, which includes theories that depart from Neo-Institutionalism. So that in its analysis, this research will look at the regulations, the bio-physical environment, the attributes of the actor community, the action arena, the action situation, and the results of decisions in the Sukoharjo District PPK selection process. This study uses a qualitative approach to research with interview data collection techniques and documentation. The results showed that the KPU of Sukoharjo Regency in carrying out the PPK selection process was normative or in accordance with the template from the RI KPU, and in determining participants who passed the PPK selection, they still tended to consider the track record or organizational background, which is certainly prone to the phenomenon of